The Boundedness of Marcinkiewicz Integral Associated with Schrödinger Operator and Its Commutator. (8th May 2014) - Chen, Dongxiang; Zou, Dan
Abstract : The authors prove that Marcinkiewicz integral operator is not only are bounded onL p, for1 < P < ∞, but also a bounded map fromL 1 ( R n ) to weakL 1 ( R n ) . Meanwhile, theB M O L -boundedness and( H L 1, L 1 ) -boundedness are also obtained. Finally, theL p -boundedness and( L ∞, B M O L ) -boundedness for the commutator of Marcinkiewicz integral of schrödinger type are established.